Interleukin‐8, interleukin‐1β and tumour necrosis factor‐α in sequential units of packed red blood cells collected from retired racing Greyhounds. Issue 1 (January 2017) - Purcell, SL; Claus, M; Hosgood, G; Smart, L
Abstract : Background: We hypothesised that concentrations of interleukin‐8 (IL‐8), interleukin‐1β (IL‐1β) and tumour necrosis factor‐α (TNF‐α) would increase during storage in the third sequential unit (U3) of canine packed red blood cells (PRBC) collected from terminal donors in haemorrhagic shock. We further hypothesised that leucoreduction would prevent cytokine accumulation in U3 and that cytokine concentrations in U3 would be higher than in the first units (U1) collected from the same dogs. Methods: U1 and U3 were each collected from 12 anaesthetised healthy Greyhounds. Removal of leucocytes from half of each PRBC unit produced one leucoreduced (LR) and one non‐leucoreduced (NLR) unit. Canine IL‐8, IL‐1β and TNF‐α concentrations were measured in samples collected from the units during storage on days 0, 10, 20, 30 and 37. Results: The IL‐8 concentration in U3 NLR units was significantly higher on days 10, 20, 30 and 37 than on day 0 and was significantly higher than in the LR units at all time points. The IL‐1β concentration in U3 did not change over time, or between LR and NLR units. TNF‐α was not detected in any unit. There were no significant differences in IL‐8 or IL‐1β concentrations between U3 and U1 at any time point; however, some NLR U3 units had markedly elevated IL‐8 concentrations at day 37 (2060–20, 682 pg/mL) compared with NLR U1 units (3369–5280 pg/mL). Conclusion: NLR U3 units collected from dogs in haemorrhagic shock showed a significant increase in IL‐8 concentrations during storage. Leucoreduction was effective at preventing the accumulation of IL‐8. There was no difference detected between U3 and U1.